The dark Sahara : America's war on terror in Africa - Keenan, Jeremy, 1945- (Pluto Press, 2009)
The US is keen to build a substantial military presence in Africa, citing the need to combat the growth of Al-Qaeda in Somalia, Algeria and other countries on the continent. This book reveals the secret US agenda behind the war on terror.